Bencana dan Konflik: Pelajaran dari Aceh dan Sri Lanka - Anita Afriani Sinulingga; Abdul Halim; Putiviola Elian Nasir (Andalas Journal of International Studies (AJIS), 2020)
Several academic studies have given birth to the notion that natural disasters and conflicts have a close relationship. Under certain conditions, the disaster functions to bring peace in conflict areas. However, it has not explained how the peace process can affect the dynamics of conflict. This paper aims to analyze the factors that cause conflict in a disaster area to transform into peace or vice versa. The prolonged social conflicts in the Indonesian provinces of Aceh (1976–2005) and Sri Lanka (1983–2009) are examples of cases where the tsunami disaster in December 2004 led to a peace agreement in Aceh, which was not long in the future while failing to bring peace to Sri Lanka. The research conduct with descriptive qualitative methods and internet-based literature study techniques. This paper finds that disaster is a catalyst for the peace process, not determining peace. The transformation of conflict into peace influence by four factors: poverty, state capacity, negotiations, and internationalization of conflicts. These factors that can create peace also depend much on pre-disaster and post-disaster peace efforts.